1994
DOI: 10.1007/bf00002569
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of nitrous oxide and methane from nitrogen-amended soils in a Colorado alpine ecosystem

Abstract: Abstract. In order to determine the effect of increased nitrogen inputs on fluxed of NaO and CH4 from alpine soils, we measured fluxes of these gases from fertilized and unfertilized soils in wet and dry alpine meadows. In the dry meadow, the addition of nitrogen resulted in a 22-fold increase in N7.0 emissions, while in the wet meadow, we observed a 45fold increase in N20 emission rates. CH4 uptake in the dry meadow was reduced 52% by fertilization; however, net CH4 production occurred in all the wet meadow p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 18 publications
4
24
0
Order By: Relevance
“…6). These results are similar to those reported by other researchers who have shown increases in N 2 O flux that usually occur within a few hours to days after precipitation events (Binstock 1984;Sexstone et al 1985;Neff et al 1994). The N pool in soil is expected to play a role in regulating the N 2 O emissions.…”
Section: Comparison With Other Ecosystemssupporting
confidence: 91%
See 2 more Smart Citations
“…6). These results are similar to those reported by other researchers who have shown increases in N 2 O flux that usually occur within a few hours to days after precipitation events (Binstock 1984;Sexstone et al 1985;Neff et al 1994). The N pool in soil is expected to play a role in regulating the N 2 O emissions.…”
Section: Comparison With Other Ecosystemssupporting
confidence: 91%
“…The average nitrate content of 1.3 mg N kg dry soil -1 and average ammonium content of *14 mg N kg dry soil -1 are similar to those reported by Williams et al (1996) and Neff et al (1994) for the growing season at a nearby dry alpine meadow at Niwot Ridge. Compared to a subalpine meadow soil (Cryorthent) in the European Alps (Freppaz et al 2007), ammonium content at NWT is similar and nitrate is one order of magnitude lower.…”
Section: Soil Nitrogen Poolssupporting
confidence: 83%
See 1 more Smart Citation
“…) (West et al, 1999;Neff et al, 1994;Whalen and Reeburgh, 1990). However, the net oxidation rates in this study were comparable with the range observed from arctic tundra ecosystems (Whalen and Reeburgh, 1992;Christensen, 1993).…”
supporting
confidence: 52%
“…Many studies have reported increased litter decomposition rates as a result of N fertilization of forests I (Aber et al, 1989;Fenn, 1991), while other studies have reported slower decomposition (Adams and Angradi, 1996;Magill and Aber, 1998). Finally, there is some evidence that elevated N deposition may also inhibit methane production (Neff et al, 1994;West et al, 1998). For policy makers, this area probably needs more research to refine numbers and extend our understanding to other natural ecosystems.…”
Section: Carbon Cycling and Utilizationmentioning
confidence: 99%